Decommissioning and radioactive waste management - Rahman, A. (Whittles Pub. ; CRC Press, 2008)
Annotation This is the most comprehensive and up-to-date book which provides a detailed understanding of all aspects of the subject, from radiological protection and nuclear safety to legislation and practical issues.
Keywords: Radioactive waste disposal.; Radioactive waste sites -- Cleanup.; elektronické knihy; electronic books